Interventional functional diagnostics in gastrointestinal endoscopy: Combining diagnostic and therapeutic tools in the endoscopy suite with the functional lumen imaging probe - Vackova, Zuzana; Levenfus, Ian; Pohl, Daniel (Current opinion in pharmacology, 2023)
With technical progress of gastrointestinal functional testing, there has been a demand for more comprehensive examination of esophageal physiology and pathophysiology beyond high-resolution manometry. A new interventional technology based on impedance planimetry, the functional lumen imaging probe (FLIP), enables intraluminal measurement of distensibility and compliance of hollow organs. EndoFLIP uses balloon catheters to measure diameter and distension pressure to calculate cross-sectional area and distensibility in different organs (mostly esophagus, stomach, anorectal region) and can be used in wide variety of indications (diagnostics, pre- and post-treatment evaluation) and currently serves as a helpful adjunctive tool in ambiguous clinical cases. EsoFLIP is a therapeutic variation that uses a stiffer balloon catheter allowing for dilation. The trend to simplify the clinical process from diagnosis to treatment tends to a one-session procedure combining diagnostics and therapeutic interventions. In specified conditions like e.g. achalasia or gastroparesis, a combination of EndoFLIP and EsoFLIP procedures may therefore be useful. The aim of this narrative review is to introduce the clinical use of FLIP and its potential benefit in combined diagnostic-therapeutic procedures.
Keywords: achalázie jícnu; Esophageal Achalasia; lidé; Stomach; Endoscopy, Gastrointestinal; žaludek; Manometry; manometrie; gastrointestinální endoskopie; Humans